Measurement of B0-B-0 flavor oscillations in hadronic B0 decays. - Aubert, B; Boutigny, D; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Robbe, P; Tisserand, V; Palano, A; Pompili, A; Chen, G; Chen, J; et al. (2002)
Flavor oscillations of neutral B mesons have been studied in e+e- annihilation data collected with the BABAR detector at center-of-mass energies near the upsilon(4S) resonance. The data sample used for this purpose consists of events in which one B0 meson is reconstructed in a hadronic decay mode, while the flavor of the recoiling B0 is determined with a tagging algorithm that exploits the correlation between the flavor of the heavy quark and the charges of its decay products. From the time development of the observed mixed and unmixed final states, we determine the B0-B-0 oscillation frequency deltamd to be 0.516+/-0.016(stat)+/-0.010(syst) ps-1.